Designing Appropriate Linguistic Research for Endangered Languages - Alkatiri, Zeffry; Siregar, Bahren Umar (Budapest International Research and Critics University, 2022)
Research is an essential element in the process of language preservation. The role of research in the language field is to develop the use of language as a medium of knowledge. Language as a communication tool has several functions, one of which is a cognitive function: language users can convey thoughts. This research conducts the process using mixed analysis methods. Retrieval of field data, which then goes through a process of classification, analysis, and conclusion in the end, must be acculturated with data taken from reference literature. Qualitative and quantitative methods are maximized to get the best results in each process. The existence of language as a medium of knowledge is realized if a language does not lose its character. One strategy that can be used in researching languages, especially those that are endangered, is Sociosemiotic or Social Semiotic. Sociosemiotic as a framework is very important to read the signs and symbols that live and are dynamic in society. These sign and symbol variables are the key to determining the success of analyzing and concluding problems and their solutions.